LAW ENFORCEMENT AGAINST THE PERPETRATORS OF ONLINE GAMBLING HIGGS DOMINO BASED ON QANUN ACEH NUMBER 6 OF 2014 CONCERNING JINAYAT LAW - Teuku Oki Ama Arispan; Nouvan Moulia (Jurist Argumentum: Pemikiran Intelektual Hukum, 2023)
As technology advances, criminal acts in gambling cases have developed, previously it was done in secret but now it can be done openly anywhere, the Higgs Domino online game has emerged and is categorized as a type of gambling act in recent years. in West Aceh Regency and law enforcement officers have arrested some of the perpetrators, but in reality there are still many members of society who carry out this gambling. This study aims to find out how law enforcement is and also the constraints that influence law enforcement carried out by law enforcement officials in West Aceh District against higgs domino online gambling actors based on Qanun Jinayat. This research is an empirical legal research that uses qualitative methods, data obtained through interviews and field observations.The research results show that law enforcement is carried out by the Police by means of appeals, collaboration with shop owners, patrols, joint raids and arrests. The Prosecutor's Office uses legal counseling and a program for prosecutors entering schools, while the Syar'iyah Court uses examination and adjudication, while the Satpol PP and WH use the WH Friday Khatib program, patrols and joint raids. Factors that hinder law enforcement are the large legal area, the site is still easily accessible, the public's lack of legal awareness, the public's unwillingness to cooperate, and several obstacles faced by police investigators. Suggestions in this study, the police need to work together with the ministry of communication and information technology to create a sophisticated tool that can detect, track and also remove sites that contain gambling, including the higgs domino online game. To the West Aceh District Government to create a special task force and provide infrastructure, special training for the task force in mastering technology in order to deal with gambling that arises with various variations.